الطريقة القادرية الشاذلية كمنهج الدعوة الإسلامية لمعهد "منهل الناشئين" الإسلامي - Nurul Hayati (Al-Zahra : Journal for Islamic and Arabic Studies, 2022)
The current modernization brings considerable changes to the entire Indonesian life, the especially Muslim community in Jakarta. Today the Muslim community in the capital of Indonesia seem to experience decadency, especially in terms of ethics, manners, association, lifestyle and care for fellow Muslim people who are increasingly indifferent. Another negative impact that is very concerning is the change that tends to lead to a moral crisis in Muslim society today, especially in the younger generation, such as the phenomenon of a free lifestyle, television broadcasts containing films that provoke the Muslim to date, pornography and porn-action. Those give rise to many complex problems that hit the country due to moral degradation.